Efforts to establish indigenous technology for healthcare in a low resource country – Bangladesh experience (Bangladesh Journal of Medical Physics, 2021)
The astounding developments in healthcare technology is not available to about 84% of the global population in the low-medium income countries (LMIC). Good meaning medical equipment donation programmes from the high income countries (HIC) have made very little impact, most devices failing to give the desired service and increasing e-waste. The author, with his four decade-long experience feels that people in the LMICs with higher education in science and technology should be motivated and trained in the design and manufacture of medical devices, and they should also take the responsibility for commercial manufacture and distribution of the developed products. With this realisation early in life, he initiated similar efforts in his home country Bangladesh about four decades back against many challenges and obstacles. This produced some success stories and this paper lists some of the devices developed and distributed by groups under his leadership. The author argues that the existing industries in the LMICs are based on fully foreign technology, and do not have the capability or preparedness to take up commercial manufacture of indigenously developed technology based products. He has come up with the design of a ‘Micro-eco-system’ for the LMICs which involve the leadership of a single technology innovator or a single group of innovators to organise R&D and commercial manufacture, both. An LMIC may have hundreds or thousands of the above ‘Micro-eco-system’ to create an overall eco-system, which may be the solution eventually leading to a more equitable world, with each and every person of the globe having access to developments in science and technology in healthcare.Bangladesh Journal of Medical Physics Vol.14 No.1 2021 P 1-15